Turmeric - maize and onion intercropping systems. I. Yield and land use efficiency - PALANIAPPAN, K SIVARAMAN, S P (Journal of Spices and Aromatic Crops, 1994)
Experiments were laid out at Bhavanisagar (Tamil Nadu, India) during 1989 - 90 and at Coimbatore (Tamil Nadu, India) during 1990 - 91 to determine land use efficiency, yield and yield attributes of turmeric (Curcuma longa L.) and maize (Zea mays L.) in various jntercropping and sole cropping systems. Turmeric, maize and onion (Allium cepa L.) were raised as sole crops adopting recommended package of practices. Maize and onion were intercropped with turmeric in two proportions (50 and 100 per cent of the recommendedpopulation levels). Onion was also introduced as additional intercrop with maize with 23 per cent of the population of sole crop. Turmeric yields were reduced from 9 to 25 per cent when intercropped with maize. Turmeric yield reductions due to intercropping were associated with reduction in number of tillers, mother rhizome, primary and secondary rhizomes. Maize yields were higher with intercropping than with sole cropping. Even though yield of turmeric was reduced by intercropping, turmeric - maize and onion intercropping resulted in 17 to 34 per cent greater land use efficiency for the 9 months growing season than in· the sole cropping systems. This is important in developing countries where available per capita arable land is low.